A comparative study of functional outcome following internal fixation and conservative management: in non-union clavicle - Patra, Saroj Kumar; Patro, Bishnu Prasad; Sahu, Mahesh Chandra; Samal, Sidharth (International Surgery Journal, 2016)
Background: Clavicle is the only long bone which is horizontally placed and known for its unique characteristics. Clavicle fracture accounts for almost 2% of total fractures. Most fractures occur in middle third of clavicle and common in young male patients. As of literature 15% clavicle fracture leads to non -union with decrease functional outcome and decreased Constant and DASH shoulder score. Most orthopedician prefer conservative management unless otherwise definitive indications for surgery like compound fracture or gross displacement with tenting of skin. We tried to find out the functional impairment following non-union of clavicle and its outcome following internal fixation and conservative management. Methods: In a prospective study 15 patients of non-union clavicle were treated either by internal fixation with bone grafting or by conservative method as per patient will. Six patients were treated with LCDCP with cancellous iliac bone graft and nine patients by conservative management. Constant shoulder score and DASH score of all patients were taken at 2, 6 and 12 month. Both the groups were compared in terms of functional outcome and radiological union. Besides we tried to found out the cause of non-union retrospectively with previous mode of management and old radiographs. Results: We had operated six patients with Plate and screws with cancellous bone graft and rest nine patients by conservative management. At one year follow up operated patients had significant improvement in DASH and Constant shoulder scores with good radiological union compared to the conservative patients. Conclusions: All young patients with displaced middle 1/3rd clavicle fractures should be considered for surgical fixation. Patient with non-union of clavicle with compromised shoulder function can also return to their normal shoulder function following surgery. Plate screw with bone grafting had good results in all six cases. In the conservative group shoulder function was always less in the affected side compared to their normal side.